An Ideal Formulation of the Prohibition on Dual Positions for Advocacy Organization Leaders from the Perspective of Legislation - Andri Darmawan; KMS Herman (Ridwan Institute, 2026)
This study examines the formulation of an ideal prohibition on dual positions for leaders of advocacy organizations who concurrently serve as state officials, addressing potential conflicts of interest and threats to organizational independence. The background stems from Article 28, paragraph (3) of Law No. 18 of 2003 on Advocates, which limits dual positions only with political party leaders and lacks explicit provisions regarding state officials, potentially undermining the independence of advocate organizations and constitutional guarantees of legal certainty and freedom of association. The study aims to provide a normative framework for legislative reform that ensures structural integrity and professional independence. Employing a normative juridical research method, the study utilized statutory and conceptual approaches, analyzing relevant constitutional provisions, statutory laws, and Constitutional Court decisions, including Numbers 014/PUU-IV/2006, 91/PUU-XX/2022, and 183/PUU-XXII/2024. Data were collected through systematic document review and legal content analysis. The results indicate that current regulations inadequately address dual positions, leaving room for structural conflicts of interest. The discussion emphasizes the necessity of reformulating Article 28(3) with clear, non-interpretable norms, operational mechanisms, and harmonization with broader legal principles. The study concludes that legislative amendments are essential to prevent conflicts, strengthen advocate independence, and maintain constitutional and rule-of-law standards in Indonesia.